Formation of a fine-dispersed liquid-metal target under the action of femto- and picosecond laser pulses for a laser-plasma radiation source in the extreme ultraviolet range. (January 2016) - Vinokhodov, A.Yu.; Koshelev, K.N.; Krivtsun, V.N.; Krivokorytov, M.S.; Sidelnikov, Yu.V.; Medvedev, S.V.; Kompanets, V.O.; Melnikov, A.A.; Chekalin, S.V.
Abstract: We report the results of studying the dynamics of deformation and fragmentation of liquid-metal droplets under the action of ultrashort laser pulses. The experiments have been performed to optimise the shape of the droplet target used in extreme ultraviolet (EUV) radiation sources based on the laser-produced plasma using the pre-pulse technology. The pre-pulse is generated by a system incorporating a master Ti : sapphire oscillator and a regenerative amplifier, allowing one to vary the pulse duration from to . The power density of laser radiation at the droplet target, averaged over the pulse duration and spatial coordinates, has reached . The production of liquid-metal droplets has been implemented by means of a droplet generator based on a nozzle with a ring piezoceramic actuator. The droplet material is the eutectic indium – tin alloy. The droplet generator could operate in the droplet and jet regime with a maximal rate of stable operation 5 and, respectively. The spatial stability of droplet position of its diameter is achieved. The size of the droplets varied within, their velocity was depending on the operation regime.